A multicenter study of body mass index in cancer patients treated with anti-PD-1/PD-L1 immune checkpoint inhibitors: when overweight becomes favorable. Issue 1 (27th February 2019) - Cortellini, Alessio; Bersanelli, Melissa; Buti, Sebastiano; Cannita, Katia; Santini, Daniele; Perrone, Fabiana; Giusti, Raffaele; Tiseo, Marcello; Michiara, Maria; Di Marino, Pietro; Tinari, Nicola; De Tursi, Michele; et al.
Abstract : Background: Recent evidence suggested a potential correlation between overweight and the efficacy of immune checkpoint inhibitors (ICIs) in cancer patients. Patients and methods: We conducted a retrospective study of advanced cancer patients consecutively treated with anti-PD-1/PD-L1 inhibitors, in order to compare clinical outcomes according to baseline BMI levels as primary analysis. Based on their BMI, patients were categorized into overweight/obese (≥ 25) and non-overweight (< 25). A gender analysis was also performed, using the same binomial cut-off. Further subgroup analyses were performed categorizing patients into underweight, normal weight, overweight and obese. Results: Between September 2013 and May 2018, 976 patients were evaluated. The median age was 68 years, male/female ratio was 663/313. Primary tumors were: NSCLC (65.1%), melanoma (18.7%), renal cell carcinoma (13.8%) and others (2.4%). ECOG-PS was ≥2 in 145 patients (14.9%). PD-1/PD-L1 inhibitors were administered as first-line treatment in 26.6% of cases. Median BMI was 24.9: 492 patients (50.6%) were non-overweight, 480 patients (50.4%) were overweight/obese. 25.2% of non-overweight patients experienced irAEs of any grade, while 55.6% of overweight/obese patients ( p  < 0.0001). ORR was significantly higher in overweight/obese patients compared to non-overweight (p < 0.0001). Median follow-up was 17.2 months. Median TTF, PFS and OS were significantly longer for overweight/obese patients in univariate (p < 0.0001, for all the survival intervals) and multivariate models ( p  = 0.0009, p < 0.0001 and p < 0.0001 respectively). The significance was confirmed in both sex, except for PFS in male patients ( p  = 0.0668). Conclusions: Overweight could be considered a tumorigenic immune-dysfunction that could be effectively reversed by ICIs. BMI could be a useful predictive tool in clinical practice and a stratification factor in prospective clinical trials with ICIs.